Distribution characteristics of spring maize meteorological drought in different climatic regions of Inner Mongolia based on standardized precipitation evapotranspiration index - Yang, Xiujuan; Qiao, Shuaishuai; Yang, Feng; Huang, Yuyuan; Han, Congying; Chang, Xiao; Hao, Shuiyuan; Qian, Hui; Feng, Xinwei; Li, Na (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Drought is a major meteorological disaster that affects the growth of spring maize in Inner Mongolia. Understanding the spatiotemporal characteristics of drought is crucial for maintaining crop production. This study categorized Inner Mongolia into five climatic regions based on geography and climate characteristics: hyper-arid, arid, semi-arid, dry and semi-humid, and moist and semi-humid, reflecting Regions I to V, respectively. Based on data collected from 107 meteorological stations, the standardized precipitation evapotranspiration index (SPEI) was used to assess the characteristics of drought occurrence in different climatic regions during the spring maize growing season over the past 60 years, as well as the impact of drought on yield. SPEI decreased across all regions during growth periods, with mid-growth stages showing the smallest decline and a slight slowdown in drought severity. Spatially, 15 stations showed reduced drought during the early growth stage, which increased to 20 stations during the mid-growth stage. The overall drought trend of intensification was obtained across various climate regions, with Region I showing the most severe drought. The drought frequency during the growth period of spring maize ranged from 20% to 42%, and the drought frequency decreased from light drought, moderate drought, and severe drought to extreme drought. The drought range in each growth stage increased, with localized and regional drought dominating the region. The drought intensity also increased. Precipitation is the main factor affecting spring maize yield, and water replenishment during the early and middle stages of growth is crucial. These findings provide a basis for efficient water resource management in the region.